2011
DOI: 10.1007/s11064-011-0594-z
|View full text |Cite
|
Sign up to set email alerts
|

The Cannabinoid WIN 55212-2 Mitigates Apoptosis and Mitochondrial Dysfunction After Hypoxia Ischemia

Abstract: Perinatal hypoxia-ischemia has significant mortality and morbidity due to there is still no specific treatment as a consequence of the complexities of hypoxic-ischemic pathophysiology. The aim of this work was to evaluate the effects of the cannabinoid agonist WIN 55212-2 on apoptotic cell death and mitochondrial dysfunction after perinatal asphyxia in fetal lambs. Animals were assigned to: one SHAM group and two hypoxic-ischemic groups that received a dose of 0.01 μg/kg WIN 55,212-2 (HI + WIN) or not (HI + VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 83 publications
(106 reference statements)
0
14
0
1
Order By: Relevance
“…The reason for this unexpected result is not clear, but may be related to peculiarities of macrophage biology in the setting of systemic CB2 deficiency. Several other studies have shown anti-apoptotic effects of WIN55,212-2 in murine models of ischemia reperfusion injury via activation of CB2 [46, 47]. Alternatively, it is possible that WIN55,212-2 treatment resulted in CB2 receptor internalization [48], which would mimic CB2 deficiency in lesional macrophages and reduce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this unexpected result is not clear, but may be related to peculiarities of macrophage biology in the setting of systemic CB2 deficiency. Several other studies have shown anti-apoptotic effects of WIN55,212-2 in murine models of ischemia reperfusion injury via activation of CB2 [46, 47]. Alternatively, it is possible that WIN55,212-2 treatment resulted in CB2 receptor internalization [48], which would mimic CB2 deficiency in lesional macrophages and reduce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In newborn rats exposed to severe anoxia or to acute hypoxiaischemia [66,67], postinsult administration of WIN55212-2 afforded a strong neuroprotective effect, abolished by either CB 1 R or CB 2 R antagonists, too, as well as increasing neuronal and oligodendroglial cell proliferation in the subventricular zone 7 days after neonatal HI in rats [68]. In term fetal lambs exposed to HI damage by umbilical cord occlusion, postinsult administration of WIN55212-2 improved cerebral blood flow and reduced astrocytic, as well as apoptotic neuronal, death-those effects relying on the preservation of mitochondrial integrity and functionality [69]. These neuroprotective effects were also afforded with CBD, the major nonpsychoactive component of Cannabis sativa, again in animal models of newborn HI encephalopathy [70][71][72][73][74].…”
Section: Cannabinoids and Brain Damage In The Immature Brain: Neonatamentioning
confidence: 96%
“…Even though we have not observed a deleterious role of the use of 100% oxygen ventilation [5,9,10], we cannot rule out a possible harmful effect of this oxygen concentration, an issue observed in the piglet model causing oxidative stress and a dose-dependent oxidation of DNA [21], thus is currently not advised in the clinical situation. On the other hand, we used an ultra-low dose of WIN that, despite showing protective effects in different paradigms of hypoxic-ischemic brain injury [5,9,10], was not enough to activate CB2Rs and was considered to be involved in the antioxidant effects of CBs. WIN showed a higher preference towards CB1Rs (Ki values: 62.3 and 3.3 nM for the human cloned CB1 and CB2 receptors, respectively), whose activation can promote rather than inhibit oxidative stress [22,23].…”
Section: Discussionmentioning
confidence: 64%
“…WIN 55,212-2 (WIN) is a potent CB1R/CB2R mixed synthetic agonist with a slightly higher CB2R selectivity compared to other mixed agonists [8]. Our results suggest that the administration of WIN after perinatal asphyxia in fetal lambs reduced brain injury, decreasing both delayed cell death and glial damage [9], together with the maintenance of mitochondrial integrity and functionality [10].…”
Section: Introductionmentioning
confidence: 82%